The Contribution of the Predicted Sorting Platform Component HrcQ to Type III Secretion in Xanthomonas campestris pv. vesicatoria Depends on an Internal Translation Start Site - Otten, Christian; Seifert, Tanja; Hausner, Jens; Büttner, Daniela (Frontiers in Microbiology, 2021)
Pathogenicity of the Gram-negative bacterium Xanthomonas campestris pv. vesicatoria depends on a type III secretion (T3S) system which translocates effector proteins into plant cells. T3S systems are conserved in plant- and animal-pathogenic bacteria and consist of at least nine structural core components, which are designated Sct (secretion and cellular translocation) in animal-pathogenic bacteria. Sct proteins are involved in the assembly of the membrane-spanning secretion apparatus which is associated with an extracellular needle structure and a cytoplasmic sorting platform. Components of the sorting platform include the ATPase SctN, its regulator SctL and pod-like structures at the periphery of the sorting platform consisting of SctQ proteins. Members of the SctQ family form a complex with the C-terminal protein domain, SctQC, which is translated as separate protein and likely acts either as a structural component of the sorting platform or as a chaperone for SctQ. The sorting platform has been intensively studied in animal-pathogenic bacteria but has not yet been visualized in plant pathogens. We previously showed that the SctQ homolog HrcQ from X. campestris pv. vesicatoria assembles into complexes which associate with the T3S system and interact with components of the ATPase complex. Here, we report the presence of an internal alternative translation start site in hrcQ leading to the separate synthesis of the C-terminal protein region (HrcQC). The analysis of genomic hrcQ mutants showed that HrcQC is essential for pathogenicity and T3S. Increased expression levels of hrcQ or the T3S genes, however, compensated the lack of HrcQC. Interaction studies and protein analyses suggest that HrcQC forms a complex with HrcQ and promotes HrcQ stability. Furthermore, HrcQC colocalizes with HrcQ as was shown by fluorescence microscopy, suggesting that it is part of the predicted cytoplasmic sorting platform. In agreement with this finding, HrcQC interacts with the inner membrane ring protein HrcD and the SctK-like linker protein HrpB4 which contributes to the docking of the HrcQ complex to the membrane-spanning T3S apparatus. Taken together, our data suggest that HrcQC acts as a chaperone for HrcQ and as a structural component of the predicted sorting platform.